Discrete physiological effects of beetroot juice and potassium nitrate supplementation following 4-wk sprint interval training - Thompson, C.; Vanhatalo, A.; Kadach, S.; Wylie, L. J.; Fulford, J.; Ferguson, S. K.; Blackwell, J. R.; Bailey, S. J.; Jones, A. M. (Journal of Applied Physiology, 2018)
The physiological and exercise performance adaptations to sprint interval training (SIT) may be modified by dietary nitrate (NO-3) supplementation. However, it is possible that different types of NO-3 supplementation evoke divergent physiological and performance adaptations to SIT. The purpose of this study was to compare the effects of 4-wk SIT with and without concurrent dietary NO-3 supplementation administered as either NO-3-rich beetroot juice (BR) or potassium NO-3 (KNO3). Thirty recreationally active subjects completed a battery of exercise tests before and after a 4-wk intervention in which they were allocated to one of three groups: 1) SIT undertaken without dietary NO-3 supplementation (SIT); 2) SIT accompanied by concurrent BR supplementation (SIT + BR); or 3) SIT accompanied by concurrent KNO3 supplementation (SIT + KNO3). During severe-intensity exercise, VO2peak and time to task failure were improved to a greater extent with SIT + BR than SIT and SIT + KNO3 (P < 0.05). There was also a greater reduction in the accumulation of muscle lactate at 3 min of severe-intensity exercise in SIT + BR compared with SIT + KNO3 (P < 0.05). Plasma NO-2 concentration fell to a greater extent during severe-intensity exercise in SIT + BR compared with SIT and SIT + KNO3 (P < 0.05). There were no differences between groups in the reduction in the muscle phosphocreatine recovery time constant from pre- to postintervention (P > 0.05). These findings indicate that 4-wk SIT with concurrent BR supplementation results in greater exercise capacity adaptations compared with SIT alone and SIT with concurrent KNO3 supplementation. This may be the result of greater NO-mediated signaling in SIT + BR compared with SIT + KNO3. NEW & NOTEWORTHY We compared the influence of different forms of dietary nitrate supplementation on the physiological and performance adaptations to sprint interval training (SIT). Compared with SIT alone, supplementation with nitrate-rich beetroot juice, but not potassium NO-3, enhanced some physiological adaptations to training.